Imaging atlas for eligibility and on-study safety of potential shoulder adverse events in anti-NGF studies (Part 3) - Roemer, Frank; Hayes, C. W.; Miller, C. G.; Hoover, K.; Guermazi, A. (Osteoarthritis and Cartilage, 2015)
Despite promising results, the U.S. Food and Drug Administration (FDA) put on hold trials assessing anti-nerve growth factor (a-NGF) compounds due to concerns over accelerated rates of OA progression. The mechanism of these events is unclear but joint adverse events were observed particularly in patients using a-NGFs in combination with non-steroidal anti-inflammatory drugs (NSAIDs), suggesting that the significantly greater analgesic effect of these separate classes of drugs prompted patients to permit increased joint load without experiencing the usual pain that would limit joint stress. Development of a-NGF drugs is continuing with stringent safety criteria included in future trials as a-NGF therapies offer potential as the first new class of analgesics in many years. Potential imaging joint safety findings and exclusionary criteria for eligibility for the large weight bearing joints were presented in parts I and II of this atlas. The shoulder as a non-weight bearing joint is likely to be less affected by increased loading due to efficacious pain reduction. However, it remains prone to degeneration especially due to concomitant rotator cuff pathology and previous trauma and inflammatory disorders. This third part of the atlas illustrates imaging findings relevant for eligibility and potential joint safety findings such as osteonecrosis, incidental findings such as large cystic lesions, inflammatory disorders, bone marrow disorders and metastases.
EVALuna2:14550